Journal of political economy (Chicago University of Chicago Press, 1994)
​The journal aims to publish highly selective, widely cited articles of current relevance that will have a long-term impact on economics research. JPE's analytical, interpretive, and empirical studies in a number of areas—including monetary theory, fiscal policy, labor economics, development, micro- and macroeconomic theory, international trade and finance, industrial organization, and social economics—are essential reading for all economists wishing to keep up with substantive new research in the discipline.
​Publised biomonthly in February, April, June, August, October and Dcember Full text articles are available from JSTOR: https://www.jstor.org/journal/jpoliecon
Keywords: Economics; ECONOMICS; POLITICAL ECONOMY; ECONOMIC RECESSION; PERIODICALS